Prototyping with data - Biddulph, Matt.; Safari eBooks; O'Reilly strata making data work conference (2011 : Santa Clara, Calif.) ([United States?] : O'Reilly Media, 2011)
"If you're a new startup looking for investment, or a team at a large company seeking the green light for a new product, nothing convinces like real running code. But how do you solve the chicken-and-egg problem of filling your early prototype with real data? We'll discuss how to use open datasets and public web APIs as a proxy for the final product while you're still in the development stage." --Resource description page.
Title from title screen.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, Calif.
Electronic reproduction.
Keywords: Rapid prototyping; Electronic data processing; Electronic books